Pemanfaatan Teknologi Dalam Menigkatkan Daya Saing Usaha Homestay Di Bangka - Yulia Asiska; Novia Lestari (Institut Citra Internasional, 2026)
The growth of the tourism sector in Bangka has increased the demand for accommodations, including community-based homestays. This study aims to analyze the role of digital technology in enhancing the competitiveness of homestays, using Homestay Hidayatullah in Pangkalpinang City as a case study. The methodology employed is descriptivequalitative, utilizing direct observation, in-depth interviews, and the collection of visitor data. The results indicate that the use of digital technology remains limited to conventional promotion and manual administration, although the homestay’s occupancy rate is satisfactory, particularly during weekends and holiday seasons, driven by service quality and customer trust. Digital technology holds the potential to improve marketing, streamline the reservation process, enhance operational efficiency, and expand market reach. Key barriers include limited human resources, low digitalliteracy, a lack of supporting facilities, and a traditional mindset among managers. Therefore, the use of digital technology is a crucial strategy for enhancing the competitiveness of homestays in Bangka and supporting business sustainability in the digital era.